The influence of sodium chloride reduction on physicochemical, biochemical, 1 rheological and sensory characteristics of Mozzarella cheese - Arboatti, Ainelén Soledad (2014)
Excessive intake of sodium has been associated with harmful effects on human health. Therefore, salt reduction in manufactured products is been targeted as a way to reduce dietary sodium intake. Sodium chloride (NaCl) plays an important role in cheese, and reducing the NaCl level in cheese may adversely affect its characteristics. Our objective was to evaluate the influence of different levels of salt reduction on the physicochemical, biochemical, rheological, and sensory characteristics of Mozzarella cheese. Samples were brine-salted for different periods to obtain cheeses with different levels of salt reduction (C: control cheese; S1: cheese with 60% salt reduction, S2: cheese with 35% salt reduction). Samples were analysed during 43 days of ripening. As expected, salt flavour intensity decreased with a decrease in NaCl levels. Small differences between control and experimental cheeses due to salting condition were observed in moisture content, water activity, maturation index, αs1-casein, αs1-I-casein, crossover temperature (when the elastic component equals the viscous component) and in some sensory attributes (aroma, colour, global flavour and creaminess). No significant differences due to salting condition were observed in pH, γ-casein, β-casein degradation, activation energy (parameter that quantifies the matrix degradation with heating), residual flavour, acidity and bitter taste. Taking into account the minor differences observed after the significant salt reduction analysed, it is considered that decreasing NaCl may not jeopardise the standard Mozzarella cheese quality.